Pragmatic Features of the Speech Act of Compliment in a Turkish TV Drama - Keshavarz, Mohammad Hossein; Çetereisi, Yasemin; Asit, Gulay (Journal of Pragmatics Research, 2020)
Research on the speech act of compliment is abundant; however, studies on the characteristics of compliments in Turkish, in general, and in Turkish TV dramas, in particular, are scarce. Therefore, to fill this research gap, the present study set out to investigate the use of compliments in a popular Turkish soap opera. To achieve the purposes of this research, thirty-two episodes of a TV drama called Sahra were selected at random to be viewed and analyzed while focusing on the topics, functions, and characteristics of compliments with reference to the role of gender. Four main topics and functions, and two major characteristics of Turkish compliments emerged from the analysis of the data. Similarities and differences were also found in the use of compliments in Turkish and other languages. The findings may have implications for research on speech acts, in general, and complimenting behavior in TV dramas, in particular.Keywords: Turkish compliments; TV drama; elaboration; exaggeration; gender